Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $A$ and $B$ are positive definite matrices, and $A-B$ is also positive definite, is $B^{-1}-A^{-1}$ necessarily positive definite?

share|cite|improve this question

A more conventional proof would be something like this: Let $A^{1/2}$ be a Hermitian square root of $A$ (such a square root always exists: since $A$ is positive definite, it can be unitarily diagonalized to $UDU^\ast$; now, take $A^{1/2}=UD^{1/2}U^\ast$ where $D^{1/2}$ is the entrywise square root of the positive diagonal matrix $D$). Let let $\sim$ denotes the $\phantom{}^\ast$congruence ("star-congruence") relation, i.e. $X\sim Y$ iff $X=P^\ast Y P$ for some invertible (but not necessarily unitary) matrix $P$. Note that positive definiteness is preserved under $\phantom{}^\ast$congruence. That is, if $X\sim Y$, then $X$ is positive definite if and only if $Y$ is positive definite.

Let $C = A^{-1/2}BA^{-1/2}$. Then $C(\sim B)$ is positive definite. Hence $C=W^\ast\Lambda W$ for some unitary matrix $W$ and some diagonal matrix $\Lambda$. Now, \begin{align} A-B &= A^{1/2} (I - A^{-1/2}BA^{-1/2}) A^{1/2}\\ &\sim I - C\\ &= W^\ast(I-\Lambda)W\\ &\sim I - \Lambda,\\ B^{-1} - A^{-1} &= A^{-1/2} (A^{1/2}B^{-1} A^{1/2} - I) A^{-1/2}\\ &\sim C^{-1} - I\\ &= W^\ast(\Lambda^{-1}-I)W\\ &\sim \Lambda^{-1} - I. \end{align} So the problem boils down to the special and trivial case where $A=I$ and $B=\Lambda$.

In the above, actually we have also prove the following proposition, which is included in some textbooks:

Proposition. If $A$ is positive definite and $B$ is Hermitian, then there exists a nonsingular matrix $P$ such that $P^\ast AP=I$ and $P^\ast BP$ is diagonal.

share|cite|improve this answer

It's true. Let me write $B\ge0$ if $B$ is positive definite. First, let $B, C\ge0$ and consider $$\begin{aligned} (B+C)^{-1}&=\bigl(B^{1/2}(I+B^{-1/2}CB^{-1/2})B^{1/2}\bigr)^{-1}\\ &=B^{-1/2}(I+B^{-1/2}CB^{-1/2})^{-1}B^{-1/2}\\ &=B^{-1/2}\sum_{n=0}^\infty(-B^{-1/2}CB^{-1/2})^nB^{-1/2}, \end{aligned}$$ which holds if $C$ is small enough. So replace $C$ by $tC$ and take the derivative at $t=0$ (only the $n=1$ term takes part): $$\left.\frac{d}{dt}(B+tC)^{-1}\right|_{t=0}=-B^{-1}CB^{-1}\le0.$$ I could have done this calculation at any $t>0$, so in fact $$\frac{d}{dt}(B+tC)^{-1}\le0.$$ Integrating this from $t=0$ to $t=1$ yields $(B+C)^{-1}\le B^{-1}$. Now let $C=B-A$.

share|cite|improve this answer
How do you know that $C=B-A$ is small enough for series expansion of $(I+B^{-1/2}CB^{-1/2})^{-1}$? – user1551 Nov 14 '12 at 8:26
@user1551: I don't. But $tC$ is, for small enough $t$, and that is all I need. That said, I must admit that the proof in the question noted in the comments above as a duplicate of this one is better than mine. (I also could have polished mine a bit, making the structure clearer, but in light of that other proof, I didn't want to.) – Harald Hanche-Olsen Nov 14 '12 at 8:31

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.